Autonomous contour tracking industrial robot by using type-2 fuzzy logic - Abdul Kadir, Ahmad Muzaffar (2013)
This research is focusing on the improvement of the tracking method done for industrial robots by using On-Off method. The On-Off method is developed previously as a solution for the autonomous tracking method. The reason for improvement of the On-Off method is because the tracking error and deviation from targeted contour is exceptionally large. Improvements are done by using Artificial Intelligence methods which are Type-1 and Type-2 Fuzzy Logic Systems. The mean error and standard deviation for the tracking has been suppressed. This includes the improvement of the tracking time efficiency for the whole contour. The industrial robot selected to perform the actual tracking motion is the ABB Revolute Robot IRB1410 with 6 degree of freedom. It is to represent the realistic condition of the industrial and the real world application. For the sensor, a proximity photoelectric sensor diffused type is used for contour surface detection signal. It is chosen for its versatility in detecting any type of material used for the targeted contour surface.